Pengelolaan Limbah B3 di PT. Bina Guna Kimia Berdasarkan Permen LHK No. 6 Tahun 2021 - Nena Ayu Sabrina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
According to a UNESCO report, more than 80% of industrial wastewater containing hazardous substances is discharged without treatment. This research aims to understand the implementation of Permen LHK Number 6 of 2021 in the management of hazardous waste at PT Bina Guna Kimia and the role of the Semarang Regency Environmental Agency (DLH). The research uses a descriptive qualitative approach with empirical juridical methods. Data were obtained through observation, interviews, documentation, and literature studies, and validated by source triangulation and analyzed qualitatively. The results showed that PT Bina Guna Kimia has implemented Permen LHK No. 6 of 2021 well, although there are still challenges such as the lack of understanding of employees about waste classification. The B3 waste management system in this company is quite effective with strict procedures in identification, storage, transportation, recording through logbooks, and real-time monitoring through the SIMPEL application. The company also regularly conducts training and works with certified vendors. DLH Semarang Regency plays an active role through supervision, socialization, compliance audits, coaching, and education to businesses to increase environmental awareness and compliance. This study suggests that DLH and PT Bina Guna Kimia improve education and training programs, and encourage industry players to seek alternative funding for the implementation of environmentally friendly technology. In addition, collaboration between stakeholders needs to be improved to create effective and sustainable hazardous waste management.